Advancement of green technologies: A comprehensive review on the potential application of microalgae biomass. (October 2021) - Yap, Jiunn Kwok; Sankaran, Revathy; Chew, Kit Wayne; Halimatul Munawaroh, Heli Siti; Ho, Shih-Hsin; Rajesh Banu, J.; Show, Pau Loke
Abstract: Microalgae have drawn significant interest worldwide, owing to their enormous application potential in the green energy, biopharmaceutical, and nutraceutical industries. Many studies have proved and stated the potential of microalgae in the area of biofuel which is economically effective and environmentally friendly. Besides the commercial value, the potential of microalgae in environmental protection has also been investigated. Microalgae-based process is one of the most effective way to treat heavy metal pollution, compared to conventional methods, it does not release any toxic waste or harmful gases, and the aquatic organism will not receive any harmful effects. The potential dual role of microalge in phytoremedation and energy production has made it widely explored for its capability. The interest of microalgae in various application has motivated a new focus in green technologies. Considering the rapid population growth with the continuous increase on the global demand and the application of biomass in diverse field, significant upgrades have been performed to accommodate green technological advancement. In the past decade, noteworthy advancement has been made on the technology involving the diverse application of microalgae biomass. This review aims to explore on the application of microalgae and the development of green technology in various application for microalgae biomass. There is great prospects for researchers in this field to delve into other potential utilization of microalgae biomass not only for bioremediation process but also to generate revenues from microalgae by incorporating clean and green technology for long-term sustainability and environmental benefits. Graphical abstract: Image 1 Highlights: Green technology is demanded to substitute energy production for sustainable economy. Microalgae display greater sustainable and commercial advantages. Development in microalgae technology have unlocked a broad range of applications. Advancement of green technology utilizing microalgae.